Heparanase 2 attenuates head and neck tumor vascularity and growth - Gross-Cohen, Miriam (Cancer Res, 2016)
The endoglycosidase heparanase specifically cleaves the heparan sulfate (HS) side chains on proteoglycans, an activity that has been implicated strongly in tumor metastasis and angiogenesis. Heparanase-2 (Hpa2) is a close homolog of heparanase that lacks intrinsic HS-degrading activity but retains the capacity to bind HS with high affinity. In head and neck cancer patients, Hpa2 expression was markedly elevated, correlating with prolonged time to disease recurrence and inversely correlating with tumor cell dissemination to regional lymph nodes, suggesting that Hpa2 functions as a tumor suppressor. The molecular mechanism associated with favorable prognosis following Hpa2 induction is unclear. Here we provide evidence that Hpa2 overexpression in head and neck cancer cells markedly reduces tumor growth. Restrained tumor growth was associated with a prominent decrease in tumor vascularity (blood and lymph vessels), likely due to reduced Id1 expression, a transcription factor highly implicated in VEGF-A and VEGF-C gene regulation. We also noted that tumors produced by Hpa2 overexpressing cells are abundantly decorated with stromal cells and collagen deposition, correlating with a marked increase in lysyl oxidase expression. Notably, heparanase enzymatic activity was unimpaired in cells overexpressing Hpa2, suggesting that reduced tumor growth is not caused by heparanase regulation. Moreover, growth of tumor xenografts by Hpa2-overexpressing cells was unaffected by administration of a monoclonal antibody that targets the heparin binding domain of Hpa2, implying that Hpa2 function does not rely on heparanase or heparin sulfate